Persepsi siswa terhadap implementasi pembelajaran Bahasa Inggris sebagai Muatan Lokal di Sekolah Dasar - Meisani, Diah Royani (Didaktika, 2021)
The interaction process that begins with the perception of education actors, namely students and teachers, is one of the factors that influence the success of learning implementation, including learning English. As one of the foreign languages studied in Indonesia, many elementary schools provide English lessons as one of the local contents. This research was conducted to find out the students' perceptions of the implementation of learning English taught in elementary schools. Using descriptive qualitative research methods, this study involved 97 students from nine elementary schools in a municipality in East Java. Data were collected through questionnaires. The data analysis was done by reducing data, presenting data, and drawing conclusions. The results showed that most of the respondents (84.54%) had positive responses regarding learning English at school. There are at least three factors that influence students' interest in learning English, namely students' motivation towards English learning, teacher factors, and fun English learning activities. In addition to studying at school, as many as 63.92% of respondents provide information that they also study English outside of school. This supports learning English in schools to be more effective. On the other hand, the data from the questionnaire also show that students have difficulty in understanding English vocabulary and structure. The results of this study are expected to give recommendations to schools which include teachers and principals to improve the English learning process in order to improve students' English skills for the better and the objectives of learning English to be achieved.